Functional constipation as a neglected condition in laryngectomized patients - Şirin, Göktuğ; Şirin, Seher (Turkish Journal of Gastroenterology, 2020)
Background/Aims: When considering the quality of life of patients who undergo total laryngectomy, constipation problems are often overlooked. This study aims to determine whether surgical or concurrent chemoradiotherapy treatments matter in the development of functional constipation in patients with advanced-stage laryngeal cancer. Materials and Methods: Patients without presurgical constipation (according to Rome IV) who were treated with either surgery (n=30) or chemoradiation (n=25) were evaluated for constipation development. Interim evaluation and recommendations were made on the 3rd month. On the 3rd and 6th months, the frequency of constipation between groups was compared using the Rome IV criteria and European Organization for Research and Treatment of Cancer Quality of Life Scale-C30 constipation symptom score. Results: On the 3rd month, the frequency of constipation was higher in the surgery group than in the chemoradiation group (76.7% vs. 28%, p<0.001). On the 6th month, although still higher, the frequency of constipation decreased following the recommendations in laryngectomized patients (56.7% vs. 36%, p=0.17). C30 Constipation “yes/no” inquiry failed to detect 11 (36.6%) and 8 (26.6%) laryngectomized patients with constipation on the 3rd and 6th months, respectively. Conclusion: Constipation is more frequent and develops in the early period of postlaryngectomy. Patients seem to benefit from additional special rehabilitation recommendations. Constipation-prone laryngectomized patients should be screened with the Rome IV criteria, which effectively detect constipation.